2022
DOI: 10.1039/d2nr00646d
|View full text |Cite
|
Sign up to set email alerts
|

On-chip high ion sensitivity electrochromic nanophotonic light modulator

Abstract: Since the discovery of electrochromism, the prospect of employing various electrochromic materials for smart window glass, variable reflectivity mirrors, and large-area displays has been the main drive for such an...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…(e) FESEM image of Silicon Nitride-based Na + -ion sensor. (f) Optical transmittance as a function of time and Na + concentration with calibration curve for ion sensing [ 107 ].…”
Section: Electrochromic Device Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…(e) FESEM image of Silicon Nitride-based Na + -ion sensor. (f) Optical transmittance as a function of time and Na + concentration with calibration curve for ion sensing [ 107 ].…”
Section: Electrochromic Device Architecturementioning
confidence: 99%
“…By means of device design, recently, Hopmann et al. offered an interesting solution to overcome the low optical transmission associated with mode metal electrodes coupling in EC-based optical waveguides ( Figure 10(e) and (f) ) [ 107 ]. Here, an EC WO 3 layer is sputtered onto a Silicon Nitride waveguide cladded by Silicon Oxide.…”
Section: Electrochromic Device Architecturementioning
confidence: 99%
“…[ 7 ] While already established in smart displays and windows, electrolyte‐controlled EC effects on waveguides recently received more attention for novel applications in photonics. [ 8 ] By coating optical waveguides with EC materials, the intensity modulation is mediated by the evanescent field which appears at the waveguide borders and interacts with the surrounding materials. Furthermore, previous reports showed that the intensity modulation of the guided light is additionally enhanced by surface plasmon polariton (SPP) excitations.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, since reduction (coloring) and oxidation (bleaching) by ion migration leads to a conductivity change of the EC material, SPP excitations are switched on and off increasing the modulation effect on the guided light. [ 8,9 ] In the presented device described in Figure 1, we used PEDOT:PSS as the EC material deposited on a 40 μm wide and 5 μm high‐embedded SU‐8 waveguide. As shown in Figure 1b, both arms of the same Y‐branch were paired up together by an ion gel electrolyte, which allowed to address each arm exclusively with just one working electrode.…”
Section: Introductionmentioning
confidence: 99%